2020
DOI: 10.3390/mi11121122
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of T-Shaped Micromixers with Vortex-Inducing Obstacles in the Inlet Channels

Abstract: To enhance fluid mixing, a new approach for inlet flow modification by adding vortex-inducing obstacles (VIOs) in the inlet channels of a T-shaped micromixer is proposed and investigated in this work. We use a commercial computational fluid dynamics code to calculate the pressure and the velocity vectors and, to reduce the numerical diffusion in high-Peclet-number flows, we employ the particle-tracking simulation with an approximation diffusion model to calculate the concentration distribution in the micromixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
(91 reference statements)
2
8
0
Order By: Relevance
“…The results of the present study are very promising when compared to other related studies using complex on-chip structures for mixing procedures [ 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In some of these studies, external microelectrodes were used and integrated on the chip to generate frequency switching transverse EOF for chaotic mixing [ 15 , 24 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The results of the present study are very promising when compared to other related studies using complex on-chip structures for mixing procedures [ 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In some of these studies, external microelectrodes were used and integrated on the chip to generate frequency switching transverse EOF for chaotic mixing [ 15 , 24 ].…”
Section: Discussionsupporting
confidence: 58%
“…In some of these studies, external microelectrodes were used and integrated on the chip to generate frequency switching transverse EOF for chaotic mixing [ 15 , 24 ]. Other studies developed complex on-chip structures of T-, Zigzag, and Serpentine types [ 25 , 26 ]. Finally, some only presented the model design of the micromixer and showed the simulation results [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that by decreasing the frequency and increasing the amplitude of the magnetic field, the mixing efficiency increases, and a better distribution of particles within the channel can be achieved. Wu and Lai [34] conducted a numerical study on a T-shaped micromixer with a vortex generator obstacle at the input. They studied the effect of geometric variables such as obstacle distance and obstacle angle on micromixer performance.…”
Section: Introductionmentioning
confidence: 99%
“…The current special issue includes 12 research papers [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The topics of the papers are focused on design of micromixers [ 2 , 3 , 4 , 5 , 6 , 7 , 9 , 12 , 13 ], fabrication [ 8 , 9 , 12 ], and analysis [ 11 ]. Some of them propose novel micromixer designs [ 2 , 3 , 5 , 6 ], which include a slight modification of an existing micromixer [ 6 ].…”
mentioning
confidence: 99%
“…The topics of the papers are focused on design of micromixers [ 2 , 3 , 4 , 5 , 6 , 7 , 9 , 12 , 13 ], fabrication [ 8 , 9 , 12 ], and analysis [ 11 ]. Some of them propose novel micromixer designs [ 2 , 3 , 5 , 6 ], which include a slight modification of an existing micromixer [ 6 ]. Most of them deal with passive micromixers, but two papers [ 5 , 11 ] report the studies on electrokinetic micromixers.…”
mentioning
confidence: 99%